2016
DOI: 10.1149/2.0111608jes
|View full text |Cite
|
Sign up to set email alerts
|

Phase Structure, Electrochemical Properties and Cyclic Characteristic of a Rhombohedral-Type Single-Phase Nd2MgNi9Hydrogen Storage Alloy

Abstract: A single-phase PuNi3-type Nd2MgNi9 alloy was firstly prepared through induction melting followed by zoning annealing method, and the structural and electrochemical properties of the alloy were studied. Low-angle X-ray diffraction and Rietveld refinement analyses verify that the crystal structure of the Nd2MgNi9 alloy is the PuNi3-type super-stacking structure with a space group R-3m. It is found that the Nd2MgNi9 alloy electrode exhibits excellent electrochemical properties. The discharge capacity of the alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The smaller corrosion current density means a higher corrosion resistance. 28 Based on the calculated results, the corrosion current density of the as-cast alloy, Gd 2 Co 7 and Ce 2 Ni 7 -type alloy electrodes gradually decreases and are 61.6, 60.4 and 55.4 mA cm -2 , respectively. The results show that the corrosion resistances of the three alloy electrodes are increasingly enhanced.…”
Section: High Rate Dischargeability and Electrochemical Kinetics-fig-mentioning
confidence: 92%
“…The smaller corrosion current density means a higher corrosion resistance. 28 Based on the calculated results, the corrosion current density of the as-cast alloy, Gd 2 Co 7 and Ce 2 Ni 7 -type alloy electrodes gradually decreases and are 61.6, 60.4 and 55.4 mA cm -2 , respectively. The results show that the corrosion resistances of the three alloy electrodes are increasingly enhanced.…”
Section: High Rate Dischargeability and Electrochemical Kinetics-fig-mentioning
confidence: 92%
“…A 2 B 7 -type alloys are thought to have superior comprehensive electrochemical and hydrogen storage properties among the above-mentioned phases in La-Mg-Ni system, but the cycling stability still need to be enhanced for practical application. [6][7][8][9] Recently, Zhang et al 10 found that the Gd 2 Co 7 -type Sm 1.6 Mg 0.4 Ni 7 compound alloy shows high hydrogen storage capacity (1.88 wt%) and good cycling stability. The capacity retention rate of this compound reaches up to 99.3% at the 100th cycle and the crystal structure is intact even after 100 cycles.…”
mentioning
confidence: 99%